Christmas in Alaska - Macomber, Debbie (Mira Books, 2021)
Mail-order bride: Gold River, Alaska, isn't your average town. After being jilted by her fiancé, Caroline Myers ends up there--thanks to her matchmaking aunts, who send her on what appears to be a vacation. But Caroline didn't know that her well-meaning relatives had cooked up a scheme. Not surprisingly, they have something different in mind. Something that involves spending a snowy Christmas in ruggedly handsome Paul Trevor's home--as his Mail-Order Bride. And after gazing into Paul's dark eyes, Caroline had to agree.